Pendampingan dan Penerapan Teknologi Pengukuran Sport Performance Bagi pelatih dan Atlet Cabang Olahraga Unggulan Kabupaten Bangka Tengah - Simbolon, Muhammad Eka Mardyansyah; Firdausi, Dzihan Khilmi Ayu; Altiarika, Eka (Jurnal SOLMA, 2024)
Background: The Central Bangka Regency Government strongly supports sports activities for regional achievements. A total of 18 athletes and 7 coaches from Central Bangka Regency participated in the 2021 XX Papua PON. The role of practitioners in PON regional training is quite a concern for the Central Bangka Regency Government. It is hoped that the application of sports science in these activities can also be applied to the Central Bangka Regency Porprov Pelatda. However, KONI Central Bangka itself has limitations both in terms of  equipment and the quantity and quality of its human resources. Method: PKM assistance and application of sports performance measurement technology for coaches and athletes in leading sports in Central Bangka Regency is carried out through synergy between the Service Team (Muhammadiyah Bangka Belitung University) and Partners (KONI Central Bangka Regency). The program carried out was athlete measurements with Koni Central Bangka regional trainers totaling 168 athletes and a workshop on assistance in the use of sports performance technology for district trainers. Central Bangka. Results: Coach enthusiasm in carrying out tests and measurements of athletes using sports performance technology and following mentoring. Apart from coaches who utilize sports performance technology in coaching PORPROV VI Bangka Belitung regional athletes, Central Bangka Regency achieved overall champion achievement by winning 71 gold, 51 silver and 47 bronze medals. Conclusion: Has an impact in increasing trainers' knowledge in designing, implementing and broadcasting training programs by utilizing sports performance technology.